2019
DOI: 10.1001/jamanetworkopen.2019.10490
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Racial/Ethnic Representation Among US Medical Students

Abstract: Key Points Question Were the Liaison Committee on Medical Education 2009 diversity accreditation guidelines associated with decreased underrepresentation of minorities in medicine? Findings In this cross-sectional study of self-reported race/ethnicity of US medical school matriculants from 2002 to 2017, numbers and proportions of black, Hispanic, and American Indian or Alaska Native medical school matriculants increased, but at a rate slower than their age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
232
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(240 citation statements)
references
References 17 publications
8
232
0
Order By: Relevance
“…The self-reported demographic characteristics of interest were sex (Male and Female), race/ethnicity(Asian, Black or African American, Hispanic, Latino or of Spanish Origin, Multiple Race-Hispanic, and White). In a similar fashion to previous work, we combined Hispanic, Latino, or of Spanish Origin and those of Multiple Race-Hispanic [4]. Notably, nativity (U. S. born or non-U.…”
Section: Faculty Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The self-reported demographic characteristics of interest were sex (Male and Female), race/ethnicity(Asian, Black or African American, Hispanic, Latino or of Spanish Origin, Multiple Race-Hispanic, and White). In a similar fashion to previous work, we combined Hispanic, Latino, or of Spanish Origin and those of Multiple Race-Hispanic [4]. Notably, nativity (U. S. born or non-U.…”
Section: Faculty Datamentioning
confidence: 99%
“…This idea has been extended to the biomedical sciences [ 2 ] that scientists from diverse backgrounds and life experiences collectively offer a unique complement of innovation, creativity, and problem-solving abilities that more effectively address complex scientific problems. Despite the added value that diversity brings to scientific endeavors, the science and medicine workforce does not reflect the diversity of our nation’s populace [ 4 12 ]. Further, previous work demonstrates declining racial and ethnic representation in clinical academic medical faculty [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite longstanding awareness of the value of building a diverse physician workforce, 1 projections show that the current trainee pool still will not be representative of the US population as they enter clinical practice. 2 The representation of under-represented in medicine (URM) physicians is declining in most specialties rather than improving. 3 This is alarming as it is well-established that a diverse physician workforce improves health care access for underserved populations and increases innovation in medically relevant research.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these systemic efforts that have led to an increase in the number of those UIM, this growth is being outpaced by their relative growth within the general United States population resulting in a relative contraction of UIM [ 9 , 17 , 21 , 22 ]. Further, specific to pediatrics, while in 2018 the US population consisted of 60% non-Hispanic White, 6% Asian (including a person having origins in any of the original peoples of the Far East, Southeast Asia, or the Indian subcontinent), and 34% UIM; the AAMC reported that the racial and ethnic composition within the departments of pediatrics faculty are: 65% are non-Hispanic White, 18% Asian, and only 17% UIM [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%